2015
DOI: 10.15446/rfnam.v68n2.50985
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cassava-starch coatings with ascorbic acidic and N-acetylcysteine on the quality of harton plantain (<i>Musa paradisiaca</i>)

Abstract: The effect of coatings was evaluated on the quality of harton plantain fruits (Musa paradisiaca) in the postharvest stage. Solutions for three treatments were prepared from 50 g L-1 cassava starch (Manihot esculenta) with 30 g L-1 glycerol as the plasticizer and 6 g L-1 polyethylene glycol-600®; for anti-browning agents, 6 g L-1 ascorbic acid (AA) and 8 g L-1 N-Acetyl-Cysteine (NAC) were added. The fruits were coated by immersion, stored at 18 ± 4°C and 85% RH. Physicochemical properties were determined at 32 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…The retention effect in PEC and PEC@4 could be due to the functionality of the semi-permeability of the coating with bioactive compounds, which assisted with the moderation of the metabolic activities in the fruits and, consequently, delayed the increase of TSS contents of the coated fresh-cut fruit (Gol & Ramana Rao, 2011). A similar progressional pattern coupled with delayed increase in TSS content during storage was reported by Márquez Cardozo et al (2015) when cassava-starch coatings were applied with ascorbic acidic and N-acetylcysteine on Musa paradisiaca.…”
Section: Total Soluble Solidsupporting
confidence: 70%
“…The retention effect in PEC and PEC@4 could be due to the functionality of the semi-permeability of the coating with bioactive compounds, which assisted with the moderation of the metabolic activities in the fruits and, consequently, delayed the increase of TSS contents of the coated fresh-cut fruit (Gol & Ramana Rao, 2011). A similar progressional pattern coupled with delayed increase in TSS content during storage was reported by Márquez Cardozo et al (2015) when cassava-starch coatings were applied with ascorbic acidic and N-acetylcysteine on Musa paradisiaca.…”
Section: Total Soluble Solidsupporting
confidence: 70%
“…Total Soluble Solids (TSS) But, among the treatments there was no seen evident changes. In previously study, harton plantain (Musa paradisiaca) was coated with cassava starch-based coating material, but the authors did not found significant difference with a confidence level of 95% in the concentration of total soluble solids (TSS) (Cardozo et al 2015). The result of the present study is inappropriate with this result, but we used the fresh-cut samples, however, the authors used intact banana fruits.…”
Section: Resultsmentioning
confidence: 56%
“…The semi-permeability of the bioactive chemical coating, which helped control metabolic activities in vegetables and as a result, delayed the increase in TSS levels of the treated vegetables, could explain the retention effect of TSS of T. triangulare and T. occidentalis treated with the leaves of L. camara and maize-based coating. When cassava starch coatings containing ascorbic acid and N-acetylcysteine were applied to Musa paradisiaca, Márquez Cardozo et al (2015) observed a similar progressional trend with a delayed increase in TSS contents.…”
Section: Total Soluble Solids (Tss)mentioning
confidence: 68%